A novel highly active catalyst form CuFeMg layered double oxides for the selective catalytic reduction of NO by CO. (1st June 2022) - Liu, Jun; Zang, Pengchao; Liu, Xiaoqing; Mi, Jinxing; Wang, Ying; Zhang, Guojie; Chen, Jianjun; Zhang, Yongfa; Li, Junhua
Highlights: Cu doping can enhance the low temperature performance of CO-SCR reaction. Cu1.2 FeMg2.8 -LDO catalyst exhibited an outstanding stability and water resistance. The strong synergy between Cu and Fe plays a key role in the CO-SCR reaction. The CO-SCR reaction mechanism was proposed based on in situ DRIFT spectra and NAP-XPS. Abstract: A series of Cux FeMg4-x -LDO and Cu/FeMg2.8 -LDO catalysts were prepared by calcination of CuFeMg layered double hydroxide (LDH) for CO-SCR reaction. The Cu1.2 FeMg2.8 -LDO catalyst exhibited the highest CO-SCR activity and the NO conversion reach 100 % at 225–600 °C with a space velocity of 60000 mL·g −1 ·h −1 . The Cux FeMg4-x -LDO composite metal oxide generated by topotactic transformation not only promotes the dispersion of CuO species but also promotes the generation of Cuz Mg1-z Fe2 O4 spinel phase and the reactive oxygen species (Cu 2+ -O-Cu 2+ and Cu 2+ -O-Fe 3+ ). Moreover, it also has the high H2 consumption and more surface adsorbed oxygen, which can significantly improve the redox capacity of the catalysts. The appearance of Cu + –CO/Fe 2+ –CO species and the relatively low activation energy are also responsible for the better catalytic activity of Cu1.2 FeMg2.8 -LDO at low temperatures. Furthermore, for the CO-SCR reaction over Cu1.2 FeMg2.8 -LDO catalysts, the L-H mechanism is consistent at low temperatures and the E-R mechanism at high temperatures. This work offers insights for the rational design of highly efficient catalysts for the low temperature CO-SCR reaction.